Study of silicon pixel sensor for synchrotron radiation detection - 李贞杰 贾云丛 胡凌飞 刘鹏 殷华湘 (Chinese physics C, 2016)
The silicon pixel sensor（SPS） is one of the key components of hybrid pixel single-photon-counting detectors for synchrotron radiation X-ray detection（SRD）. In this paper, the design, fabrication, and characterization of SPSs for single beam X-ray photon detection is reported. The designed pixel sensor is a p＋-in-n structure with guard-ring structures operated in full-depletion mode and is fabricated on 4-inch, N type, 320 μm thick, high-resistivity silicon wafers by a general Si planar process. To achieve high energy resolution of X-rays and obtain low dark current and high breakdown voltage as well as appropriate depletion voltage of the SPS, a series of technical optimizations of device structure and fabrication process are explored. With optimized device structure and fabrication process,excellent SPS characteristics with dark current of 2 n A/cm~2, full depletion voltage 〈 50 V and breakdown voltage〉 150 V are achieved. The fabricated SPSs are wire bonded to ASIC circuits and tested for the performance of X-ray response to the 1W2 B synchrotron beam line of the Beijing Synchrotron Radiation Facility. The measured S-curves for SRD demonstrate a high discrimination for different energy X-rays. The extracted energy resolution is high（〈 20% for X-ray photon energy 〉 10 keV） and the linear properties between input photo energy and the equivalent generator amplitude are well established. It confirmed that the fabricated SPSs have a good energy linearity and high count rate with the optimized technologies. The technology is expected to have a promising application in the development of a large scale SRD system for the Beijing Advanced Photon Source.